Highly Sensitive Detection of Carcinoembryonic Antigen via an Electrochemical Platform Fabricated by AuNPs/Streptavidin/Reduced Graphene Oxide - Guo, Yang; Feng, Liang (Frontiers in Chemistry, 2022)
Tumor markers are one of the important indicators for early cancer diagnosis. As a new analytical method, electrochemical immunosensing analysis has the advantages of high sensitivity, good selectivity, and rapid detection, which is of great significance for the detection of tumor markers. In this work, an AuNP/reduced graphene oxide (AuNP/rGO) composite was synthesized. We used it for electrochemical sensor fabrication with the assistance of the biotin–streptavidin protein (SA) system to further amplify the signal to achieve sensitive detection of carcinoembryonic antigen (CEA). In addition, AuNPs have been incorporated due to their good electrical conductivity and biocompatibility, which can accelerate electron transfer at the electrode interface and improve the loading capacity to capture antibodies. The fabricated AuNPs/SA/rGO has a large working surface area and high material utilization ratio, which improves the catalytic capacity of H2O2 reduction and effectively amplifies the current signal. The linear range of the response current signal of the sensor toward the CEA concentration is 20 fg/ml to 200 ng/ml, and the limit of detection can achieve 6.2 fg/ml. In addition, the fabricated immunosensor has good reproducibility, selectivity, and stability.